Impact of hands‐on care on infant sleep in the neonatal intensive care unit. Issue 1 (30th June 2016) - Levy, Jennifer; Hassan, Fauziya; Plegue, Melissa A.; Sokoloff, Max D.; Kushwaha, Juhi S.; Chervin, Ronald D.; Barks, John D.E.; Shellhaas, Renée A.
Summary: Study Objectives: Sleep disruption is increasingly recognized in hospitalized patients. Impaired sleep is associated with measureable alterations in neurodevelopment. The neonatal intensive care unit (NICU) environment has the potential to affect sleep quality and quantity. We aimed: (i) to determine the frequency and duration of hands‐on care, and its impact on sleep, for NICU patients; and (ii) to assess the incidence of respiratory events associated with handling for a cohort of sick neonates. Methods: Term and near‐term neonates admitted to the NICU and at risk for cerebral dysfunction due to severity of illness or clinical suspicion for seizures underwent attended, bedside polysomnography. Continuous polysomnogram segments were analyzed and data on handling, infant behavioral state, and associated respiratory events were recorded. Results: Video and polysomnography data were evaluated for 25 infants (gestational age 39.4 ± 1.6 weeks). The maximum duration between handling episodes for each infant was 50.9 ± 26.2 min, with a median of 2.3 min between contacts. Handling occurred across all behavioral states (active sleep 29.5%; quiet sleep 23.1%; awake 29.9%; indeterminate 17.4%; P = 0.99). Arousals or awakenings occurred in 57% of contacts with a sleeping infant. Hypopnea, apnea, and oxygen desaturation occurred with 16%, 8%, and 19.5% of contacts, respectively. Hypopnea was most likely to occur following contact with infants in active sleep (28%; P < 0.001). Conclusions: Infants in the NICU experience frequent hands‐on care, associated with disturbances of sleep and respiration. The potential health and developmental impact of these disturbances merits study, as strategies to monitor sleep and minimize sleep‐disordered breathing might then improve NICU outcomes.Pediatr Pulmonol. 2017;52:84–90 © 2016 Wiley Periodicals, Inc.